Anti-Corruption from Below in Italy: Mobilization Trends from 1992 to 2021 - Rispoli, Francesca (PARTECIPAZIONE E CONFLITTO, 2024)
Using the methodology of protest event analysis and the theoretical framework of political and discursive opportunity structure, this paper analyses anti-corruption mobilizations in Italy over a 30year period (1992-2021). The chosen period is marked by a growing international interest in the topic of corruption, partly due to major political scandals. The research is based on a quantitative analysis of a dataset called Antimob, created by the author and based on press reviews. Specifically, the study investigates some characteristics of the mobilizations mapped and relates them to political and social factors, in order to assess the existence of an anti-corruption movement in Italy. By shedding light on the early stages of collective action, the article contributes the understanding of anti-corruption mobilizations in Italy.